Violence against queer people: race, class, gender, and the persistence of anti-LGBT discrimination - Meyer, Doug (Rutgers University Press, 2015)
Introduction : social inequality and violence against lesbian, gay, bisexual, and transgender (LGBT) people -- More than homophobia : the race, class, and gender dynamics of anti-LGBT violence -- I'm making Black people look bad : the racial implications of anti-queer violence -- Putting his hands on me, that made me feel very unsafe : gendered perceptions of sexual assault and physical and verbal violence -- Oh, I think it happened because I'm gay : race, gender, and perceptions of violence as homophobic -- Not that big of a deal : social class differences in viewing violence as severe -- The home and the street : violence from strangers and family members -- Conclusion : anti-queer violence and multiple systems of oppression